Multilepton signatures for leptoquarks - Éboli, O. J P [UNESP]; Funchal, R. Z.; Lungov, T. L. [UNESP] (American Physical Society (APS), 1999)
The production of third generation leptoquarks can give rise to multilepton events accompanied by jets and missing ET. In this work we study the signals of these leptoquarks at the CERN Large Hadron Collider and compare them with the ones expected in supersymmetric models. ©1998 The American Physical Society.